Using Elastographic Ultrasound to Assess the Effect of Cupping Size of Cupping Therapy on Stiffness of Triceps Muscle. (July 2021) - Jan, Yih-Kuen; Hou, Xiao; He, Xiangfeng; Guo, Chunming; Jain, Sanjiv; Bleakney, Adam
Abstract : Objective: Cupping therapy may reduce muscle stiffness for managing fatigue. However, there is no scientific evidence showing changes of muscle stiffness after cupping therapy. Furthermore, it is unclear whether the cup size of cupping therapy affects the change of muscle stiffness. The objective of this study was to compare the effect of cup size of cupping therapy on muscle stiffness. Design: A repeated measures design with a counterbalanced design was used to test three cup sizes (45, 40, and 35 mm in inner diameter) in 12 healthy participants. Strain elastography was used to measure stiffness of the triceps before and after cupping therapy at 300 mm Hg for 5 mins. Strain elastogram was converted to the grayscale for the quantification of stiffness. Results: The overall stiffness of triceps significantly reduced after cupping therapy with the 45-mm (106.2 ± 7.7, P < 0.05) and 40-mm (109.6 ± 7.1, P < 0.05) cups, but not the 35-mm cup (115.5 ± 10.3, nonsignificant) compared with before cupping (115.8 ± 13.5). The stiffness of superficial layer did not show significantly difference in all three sizes of cup. The stiffness of deep layer significantly reduced after the cupping therapy with the 45- and 40-mm cups. Conclusions: This is the first study demonstrating that cupping therapy significantly reduced muscle stiffness, especially at the deep layer.